Analisis Kinerja Jaringan Wireless Di Poltekkes Kemenkes Bengkulu - Anggita Gledisyah Putri; Khairil Khairil; Abdussalam Al Akbar (Jurnal Media Infotama, 2025)
Poltekkes Kemenkes Bengkulu, as a higher education institution in the health sector, requires fast, stable, and secure internet access to support various academic activities such as e-learning, research, and campus administration. Students and lecturers heavily rely on the wireless network to access digital resources, conduct online communication, and manage academic information. The current wireless network infrastructure at Poltekkes Kemenkes Bengkulu consists of 37 Ruijie brand Access Points (APs) distributed across the campus buildings. All APs operate on 2.4 GHz and 5 GHz frequencies and use IEEE 802.11ac/n standards to support high-bandwidth needs. These APs are utilized for academic learning activities, accessing academic resources, and administrative services for students, lecturers, and academic staff. The quality of the wireless network at Poltekkes Kemenkes Bengkulu is considered excellent, with high download and upload speeds indicating the network's capability to handle bandwidth-intensive internet activities. A ping value below 20 ms demonstrates very low latency, allowing for fast and real-time data communication. Based on the analysis using the Quality of Service (QoS) method, the results show that the wireless network performance at Poltekkes Kemenkes Bengkulu is highly satisfactory in terms of packet loss, delay, jitter, and throughput